ANALYSIS OF STUDENT RESPONSES TO USE MEDIA CARD MAGIC TOUR AND AREA OF BUILD FLAT (CLASS ROUND) FOR LEARNING MATHEMATICS SD - Dwy Nurhasana; Dwi Kameluh Agustina; Ida Putri Rarasati (JOSAR (Journal of Students Academic Research), 2019)
Based on observations and interviews conducted by the researchers, the school is still limited in the use of instructional media. Fourth grade students are still difficulties in determining the circumference and area Flat. This study aims to develop learning media Magic Card Round classes that can be used as a learning medium varied in math in elementary school. With the learning media is making the students more interested and active in the learning of mathematics in the classroom. Research conducted by the author, using the methods of research and development (R & D) model of the modified Borg and Gali. Learning media form the Magic Card Round classes that have been developed have been tested through a questionnaire validation with an average rating of 87.34% categorized as very feasible. The assessment questionnaire validation of subject matter experts with an average rating of 93.33%, amounting to 86.05% of media experts and linguists for 82.66% categorized as very feasible. Pursuant to the results of student questionnaire responses obtained by the average value of 12.76 with a maximum score of 13 with an average percentage of 98.19%. This shows the media the Magic Card Round classes eligible for use in the process of learning mathematics in fourth grade.